Early palliative care decision in patients with primary brain tumor reduces emergency department visits and hospitalization at the end of life - Nåhls, Nelli-Sofia; Anttonen, Anu; Kitti, Pauliina; Leskelä, Riikka-Leena; Akrén, Outi; Saarto, Tiina; Carpén, Timo (Springer Science and Business Media LLC, 2026)
Purpose:
Palliative care (PC) remains underutilized among patients with primary brain tumors, despite the life-threatening nature of the disease and the high symptom burden. This study aimed to assess how the timing of a PC decision (i.e., terminate life-prolonging anticancer treatments) is associated with emergency department visits and hospitalizations at the end of life (EOL).
Methods:
This single-center retrospective cohort study included adult patients (≥ 18 years) with primary brain tumor treated at the Comprehensive Cancer Center of Helsinki University Hospital during 2017–2018 who died by the end of 2018. Patients were categorized into “early PC decision” (> 30 days before death) or “late/no PC decision” (≤ 30 days or no decision). We extracted data on hospital resource use from electronic medical records.
Results:
Among 162 patients (mean age 66 years, range 24–97; 57% male), 64% had a documented PC decision, with 43% of the total cohort having an early PC decision. Patients with an early PC decision had significantly fewer emergency department visits (10% vs. 25%; p = 0.015) and fewer hospitalizations (4% vs. 29%; p < 0.001) in their final month of life compared to those with a late/no decision. Overall, 34% of patients visited a dedicated PC unit, with a median of 93 days (range 5-619) from the first PC unit visit to death.
Conclusions:
An early PC decision significantly reduced acute hospital resource use at EOL among brain tumor patients. Nonetheless, approximately one-third of patients had no documented PC decision, and similarly low numbers had PC unit visits, highlighting ongoing gaps in timely PC initiation.